Short-term effects of oral dissolving film on halitosis and oral pathogenic bacteria: a pilot non-randomized controlled trial - Cho, Mu-Yeol; Eom, Je-Hyun; Choi, Eun-Mi; Kim, Ji-Won; Kim, Young Youn; Yang, Seung-Jo; Hwang, Ju-Young; Kim, Hye-Sung (Frontiers in Microbiology, 2025)
IntroductionHalitosis is a major issue that negatively affects individuals' social interactions and quality of life. This study aimed to evaluate the effects of oral dissolving film (ODF) on halitosis and oral pathogenic bacteria.ObjectiveTo compare and evaluate the effects of ODF and tongue cleaner on reducing halitosis-related compound concentrations and oral pathogenic bacteria.MethodsA pilot, single-center, non-randomized, before-after comparative study was conducted with 30 adults with halitosis. The experimental group (n=15) consumed ODF three times daily for 7 days, while the control group (n = 15) used a tongue cleaner for the same period. H2, H2S, CH3SH, and total VSCs were measured using a halitosis analyzer, and seven oral pathogenic bacterial species were analyzed by qPCR.ResultsDue to poor compliance, one participant from each group dropped out, resulting in 28 participants included in the final analysis. In the ODF group, H2 and CH3SH significantly decreased by 55.1% and 54.4%, respectively (p < 0.05), and Streptococcus mutans also significantly decreased by 27.9% (p = 0.022). The control group did not reach statistical significance for any halitosis parameters, and Treponema forsythia significantly increased by 5.8% (p = 0.047).ConclusionODF exhibited significant reductions in key halitosis-associated compounds and demonstrated antimicrobial activity against cariogenic bacteria. This suggests ODF may serve as a convenient alternative approach for both halitosis management and dental caries prevention. Further large-scale, randomized trials are warranted to confirm these preliminary findings. This study was registered in https://trialsearch.who.int (KCT0010244).